IMPLEMENTASI TRANSFER LEARNING CONVOLUTIONAL NEURAL NETWORK UNTUK DETEKSI LUBANG JALAN PADA VIDEO DRONE - Miftahul Muhaemen; Mohammad Reza Faisal; Dodon Turianto Nugrahadi; Andi Farmadi; Rudy Herteno (Journal of Data Science and Software Engineering, 2020)
Pothole is one of the problems that can cause harm to a person or a lot of people and can even cost lives. So a lot of research has been done to detect potholes, especially image-based. This research uses Unmanned Aerial Vehicle (UAV) to get aerial video dataset and train Convolutional Neural Network (CNN) with the dataset. However, instead of doing learning from the beginning, transfer learning can be used to train CNN to recognize the object of a pothole and measure the value of its performance and what the optimal frame rate is. Then the results of this study indicate that the CNN model, ssd_resnet_50_fpn_coco gets an average performance value of 48.90 mAP. And the optimal frame rate with the average highest performance value at a frame rate of 30FPS with a value of 49.43 mAP, followed by 1FPS with a value of 48.36 mAP . Keywords: Performance, Transfer Learning, Convolutional Neural Network, Pothole Detection, Aerial Video.